Erythrocytic nuclear abnormalities in wild and caged fish (Liza aurata) along an environmental mercury contamination gradient - Guilherme, S.
Laranjo basin (Aveiro, Portugal) has been subjected to mercury contamination from a chlor-alkali plant, presenting a well-described mercury gradient. This study aims the assessment of mercury genotoxicity in this area by measuring erythrocytic nuclear abnormalities (ENA) frequency in the mullet Liza aurata, and its relation with total mercury concentration (Hgt) in blood. Wild fish were seasonally analysed, and, complementarily, fish were caged for 3 days at three locations differing on their distances to the mercury source. The results from Laranjo were compared with those from a reference area (S. Jacinto). Wild fish from Laranjo showed elevated ENA frequency in summer and autumn in concomitance with increased blood Hgt. Surprisingly, no ENA induction was found in winter, despite the highest blood Hgt, which may be explained by haematological dynamics alterations, as supported by a decreased immature erythrocytes frequency. Caged fish displayed ENA induction only at the closest site to the contamination source, also showing a correlation with blood Hgt.